If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3x * y = 3 Multiply x * y 2x + 3xy = 3 Solving 2x + 3xy = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Reorder the terms: -3 + 2x + 3xy = 3 + -3 Combine like terms: 3 + -3 = 0 -3 + 2x + 3xy = 0 The solution to this equation could not be determined.
| 5.54x+100=30.6916+10x | | 4x1/1.2 | | 3x-5+4x=-40 | | f(-5)=3x+4 | | (10a-4)= | | 6r+r=6r-5 | | 17x=1.3 | | 10/11x-9/11=4 | | 33-12x+25x=-6 | | 72+3x=7x-10 | | 7(r-9)=35 | | 1/2x^5=512 | | 72=4x-10 | | 2(2x+6)+8-3=14+11+15 | | Y-2=9(9x+6) | | b+10=6b | | 1/2×=13 | | 5x+10-15x=30 | | 9999999999999999999999999999999999999999999999999999999999999999999999999999999= | | y=4x^(2/3) | | 4(j+6)=72 | | 5x-10=440 | | -7x+6-9x=6 | | 3(5.45)-7y=3 | | 10c-14=86 | | 14y=-14x-56 | | 49+x=x^2+2x+1 | | 6p+8=62 | | -2c+1=0 | | 7x+8x=-10+5x | | 14=49y | | x+(x+1)+(x+2)=128 |